2019
DOI: 10.3389/fpls.2019.01564
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor CsWIN1 Regulates Pericarp Wax Biosynthesis in Cucumber Grafted on Pumpkin

Abstract: Pericarp wax of cucumber is an important economic trait, determining sales and marketing. Grafting of cucumber onto pumpkin rootstock (Cucurbita moschata) is an effective way to produce glossy cucumber fruits. However, the molecular regulation mechanism of this phenomenon remains largely unknown. In the present study, transcriptome analyses, genome-wide DNA methylation sequencing, and wax metabolite analysis were performed on the pericarp of self-rooted versus grafted cucumber. We identified the AP2/ERF-type t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Silicon plays a significant role in promoting crop growth and improving crop resistance to biotic and abiotic stresses [ 13 , 23 ]. Previous studies have shown significant differences in gene expression in cucumber leaves after silicon addition [ 24 , 25 ]. In this work, silicon induced the differential expression of 602 genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon plays a significant role in promoting crop growth and improving crop resistance to biotic and abiotic stresses [ 13 , 23 ]. Previous studies have shown significant differences in gene expression in cucumber leaves after silicon addition [ 24 , 25 ]. In this work, silicon induced the differential expression of 602 genes.…”
Section: Discussionmentioning
confidence: 99%
“…2′-grafted cucumber. A previous study reported that grafting increased the upregulation of the bloom transporter protein gene CsABC in cucumber [ 24 ]. This suggests that rootstocks alter fruit bloom content by affecting the bloom transporter protein activity in cucumber scions, which we have proved before.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, graft-induced protein-coding RNAs and non-coding small RNAs have been detected in the scion or rootstock of vegetables ( Ren et al, 2018 ; Miao et al, 2019 ; Wang et al, 2019a , b ; Zhang et al, 2019a , b ; Aslam et al, 2020 ; Garcia-Lozano et al, 2020 ; Spanò et al, 2020 ) as well as woody species grafts ( Cookson et al, 2013 ; Corso et al, 2015 ; Kaja et al, 2015 ; Li et al, 2016 ; Chitarra et al, 2017 ; Pagliarani et al, 2017 ). Such graft-induced transcripts have a putative role in graft development, yield, fruit quality of scions and in response to abiotic or biotic factors ( Ren et al, 2018 ; Zhang et al, 2019a , b ; Garcia-Lozano et al, 2020 ; Spanò et al, 2020 ) (described in following sections).…”
Section: Molecular Mechanisms Underlying Grafting and The Epigenetic mentioning
confidence: 99%
“…In 2019 alone, more than 20 studies were published that reported identification of new candidate genes for simply inherited mutants or QTLs in cucumber. These publications covered a variety of traits, such as resistance to cucumber vein yellowing virus (CVYV), powdery mildew and angular leaf spot (Pujol et al, 2019;Zhang et al, 2020a;2020b;2021), tolerance to abiotic stresses (heat and cold) (Dong et al, 2019;Wang et al, 2019b), plant architecture (Wen et al, 2019a;Njogu et al, 2020), flowering time, fruit size, shape, skin features, pedicel direction, and internal quality attributes (Rett-Cadman et al, 2019;Sun et al, 2019;Zhang et al, 2019Zhang et al, , 2020bGao et al, 2020;Sheng et al, 2020;Song et al, 2020;Pan et al, 2020b;Wang et al, 2020a;2020b;, and leaf color and shape mutations (Ding et al, 2019;Liu et al, 2019;Hu et al, 2020).…”
Section: B Mapped Genes and Qtls And Markerassisted Selectionmentioning
confidence: 99%